Conservation of shibire and RpII215 temperature-sensitive lethal mutations between Drosophila and Bactrocera tryoni - Nguyen, Thu N. M.; Choo, Amanda; Baxter, Simon W. (Frontiers in Insect Science, 2024)
The sterile insect technique can suppress and eliminate population outbreaks of the Australian horticultural pest, Bactrocera tryoni, the Queensland fruit fly. Sterile males mate with wild females who produce inviable embryos, causing population suppression or elimination. Current sterile insect releases are mixed-sex as efficient removal of unrequired factory reared females is not yet possible.Here we assessed known Drosophila melanogaster temperature sensitive embryonic lethal alleles shibire (G268D, shi ts1 ) and RNA polymerase II 215 (R977C, RpII215 ts ) for potential use in developing B. tryoni genetic sexing strains (GSS) for conditional removal of females. Complementation tests in D. melanogaster wild type or temperature sensitive genetic backgrounds were performed using the GAL4-UAS transgene expression system. A B. tryoni wild type shibire isoform partially rescued Drosophila temperature lethality at 29 o C by improving survivorship to pupation, whilst expressing B. tryoni shi ts1 failed to rescue the lethality, supporting a temperature sensitive phenotype. Expression of the B. tryoni RpII215 wild type protein rescued lethality of D. melanogaster RpII215 ts flies at 29 o C. Overexpressing the B. tryoni RpII215 ts allele in the D. melanogaster wild type background unexpectedly produced a dominant lethal phenotype at 29 o C. The B. tryoni shibire and RpII215 wildtype alleles were able to compensate, to varying degrees, for the function of the D. melanogaster temperature sensitive proteins, supporting functional conservation across species. Shibire and RpII215 hold potential for developing insect strains that can selectively kill using elevated temperature, however alleles with milder effects than shi ts1 will need to be considered.